2018
DOI: 10.1128/jb.00447-17
|View full text |Cite|
|
Sign up to set email alerts
|

The Novel Transcriptional Regulator LmbU Promotes Lincomycin Biosynthesis through Regulating Expression of Its Target Genes in Streptomyces lincolnensis

Abstract: Lincomycin A is a clinically important antimicrobial agent produced by Streptomyces lincolnensis. In this study, a new regulator designated LmbU (GenBank accession no. ABX00623.1) was identified and characterized to regulate lincomycin biosynthesis in S. lincolnensis wild-type strain NRRL 2936. Both inactivation and overexpression of lmbU resulted in significant influences on lincomycin production. Transcriptional analysis and in vivo neomycin resistance (Neo r ) reporter assays demonstrated that LmbU activate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
80
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(84 citation statements)
references
References 46 publications
4
80
0
Order By: Relevance
“…We suppose that an unknown regulator and SLCG_2919 might collaboratively or competitively modulate the transcription of lmbD. Recently, the CSR LmbU was shown to directly activate expression of the lmbA and lmbW genes and indirectly stimulate the expression of lmbC and lmbJ, while indirectly repressing the expression of lmbK and lmbU (10). These findings implied a more complex transcriptional regulatory mechanism of lincomycin biosynthesis than previously expected.…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…We suppose that an unknown regulator and SLCG_2919 might collaboratively or competitively modulate the transcription of lmbD. Recently, the CSR LmbU was shown to directly activate expression of the lmbA and lmbW genes and indirectly stimulate the expression of lmbC and lmbJ, while indirectly repressing the expression of lmbK and lmbU (10). These findings implied a more complex transcriptional regulatory mechanism of lincomycin biosynthesis than previously expected.…”
Section: Discussionmentioning
confidence: 64%
“…SLCG_2919 directly represses transcription of the CSR gene lmbU. The function of a positive cluster-situated regulator (CSR), LmbU, from the lincomycin biosynthetic pathway was recently described (10). To find a relationship between SLCG_2919 and LmbU, we compared transcriptional levels of lmbU between LCGL and the ΔSLCGL_2919 mutant.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the incorporation of systems for the synchronisation of immunity mechanisms to ensure protection of the whole multicellular population is now being identified with increasing frequency. The discovery of the enormous array of signalling molecules, regulatory proteins, regulatory networks and pathways in Actinobacteria has shown that evolution has solved the problem in many different ways, and undoubtedly, there are novel mechanisms still to be elucidated, such as the recently discovered novel LmbU family of CSRs, which appears to be widespread in BGCs of Actinobacteria (Hou et al, 2018).…”
Section: Concluding Remarks: Ecological and Evolutionary Implicationsmentioning
confidence: 99%
“…To date, genetic and biochemical studies have focused on elucidating the genes and enzymes responsible for synthesizing the precursors propylhygric acid (a nonproteogenic amino acid) and the sugar methylthiolincosamide and their subsequent conjugation to form the mature antibiotic (32). In this issue, Hou et al revisit the lincomycin biosynthetic pathway and shed light on its regulation (23). Bioinformatic analysis of the lincomycin gene cluster in S. lincolnensis suggested that gene lmbU encodes a novel cluster-situated regulator.…”
mentioning
confidence: 99%